Island Cotton Enhanced Disease Susceptibility 1 Gene Encoding a Lipase-Like Protein Plays a Crucial Role in Response to Verticillium dahliae by Regulating the SA Level and H2O2 Accumulation - Yan, Zhang; Xingfen, Wang; Wei, Rong; Jun, Yang; Zhiying, Ma (Frontiers in Plant Science, 2016)
Cotton is one of the most economically important crops, but most cultivated varieties lack adequate innate immunity or resistance to Verticillium wilt. This results in serious losses to both yield and fiber quality. To identify the genetic resources for innate immunity and understand the pathways for pathogen defenses in this crop, here we focus on orthologs of the central Arabidopsis thaliana defense regulator Enhanced Disease Susceptibility 1 (EDS1). The full-length cDNA of GbEDS1 was obtained by screening the full-length cDNA library of Gossypium barbadense combining with RACE strategy. Its open reading frame is 1848 bp long, encoding 615 amino acid residues. Sequence analysis showed that GbEDS1 contains a conserved N-terminal lipase domain and an EDS1-specific KNEDT motif. Expression profiling indicated that the gene is induced by Verticillium dahliae as well as salicylic acid (SA) treatment. Subcellular localization assays revealed that GbEDS1 is located in the cell cytoplasm and nucleus. Overexpression of GbEDS1 in Arabidopsis dramatically up-regulated SA and H2O2 production, resulting in enhanced disease resistance to V. dahliae. Silencing of GbEDS1 in G. barbadense significantly decreased SA and H2O2 acumulation, leading to the cotton more susceptibility. Moreover, combining the gene expression results from transgenic Arabidopsis and silenced-GbEDS1 cotton, it indicated that GbEDS1 could activate GbNDR1 and GbBAK1 expression. These findings not only broaden our knowledge about the biological role of GbEDS1, but also provide new insights into the defense mechanisms of GbEDS1 against V. dahliae in cotton.